Deficiency of the Arabidopsis Helicase RTEL1 Triggers a SOG1-Dependent Replication Checkpoint in Response to DNA Cross-Links. Issue 1 (16th January 2015) - Hu, Zhubing; Cools, Toon; Kalhorzadeh, Pooneh; Heyman, Jefri; De Veylder, Lieven
Abstract : Deficiency of the Arabidopsis RTEL1 DNA helicase activates a replication-dependent cell cycle arrest that depends on the SOG1 checkpoint regulator. Abstract: To maintain genome integrity, DNA replication is executed and regulated by a complex molecular network of numerous proteins, including helicases and cell cycle checkpoint regulators. Through a systematic screening for putative replication mutants, we identified an Arabidopsis thaliana homolog of human Regulator of Telomere Length 1 (RTEL1), which functions in DNA replication, DNA repair, and recombination. RTEL1 deficiency retards plant growth, a phenotype including a prolonged S-phase duration and decreased cell proliferation. Genetic analysis revealed that rtel1 mutant plants show activated cell cycle checkpoints, specific sensitivity to DNA cross-linking agents, and increased homologous recombination, but a lack of progressive shortening of telomeres, indicating that RTEL1 functions have only been partially conserved between mammals and plants. Surprisingly, RTEL1 deficiency induces tolerance to the deoxynucleotide-depleting drug hydroxyurea, which could be mimicked by DNA cross-linking agents. This resistance does not rely on the essential replication checkpoint regulator WEE1 but could be blocked by a mutation in the SOG1 transcription factor. Taken together, our data indicate that RTEL1 is required for DNA replication and that its deficiency activates a SOG1-dependent replication checkpoint.